PROSEDUR LAYANAN AKTIVASI APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIKKA - Yovilia Nona Yosefat; Intan Mustafa; Alfian Harbiyanto (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Digital transformation in public services has encouraged the government to develop Digital Population Identity (IKD) as an innovation in population administration. This study aims to describe and analyze the service procedures for activating the Digital Population Identity application at the Department of Population and Civil Registration of Sikka Regency, as well as to identify the obstacles encountered in its implementation. This research employs a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The research informants consist of department leaders, population administration service officers, IKD operators, and service users. The findings indicate that the IKD activation service procedures at the Department of Population and Civil Registration of Sikka Regency have been implemented in accordance with applicable regulations and technical guidelines, encompassing the stages of preparation, verification, and activation. Service officers play a crucial role as facilitators and companions for the community during the IKD activation process. However, the implementation of the service still faces several challenges, such as limited internet connectivity, insufficient human resources, and low digital literacy among certain segments of the community. Public responses to the IKD service vary, with some individuals experiencing the benefits of digital services, while others remain hesitant to adopt them. From a public service perspective, the IKD activation service represents a progressive form of e-government-based service innovation; nevertheless, its effectiveness and efficiency have not yet been fully optimized. Therefore, strengthening infrastructure, enhancing the capacity of public service personnel, and implementing continuous public outreach strategies are necessary to improve the quality of population administration services in an inclusive and sustainable manner. ABSTRAK Transformasi digital dalam pelayanan publik mendorong pemerintah untuk mengembangkan Identitas Kependudukan Digital (IKD) sebagai inovasi dalam administrasi kependudukan. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis prosedur layanan aktivasi aplikasi Identitas Kependudukan Digital di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka, serta mengidentifikasi kendala yang dihadapi dalam pelaksanaannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Informan penelitian terdiri atas pimpinan dinas, petugas pelayanan administrasi kependudukan, operator IKD, serta masyarakat pengguna layanan. Hasil penelitian menunjukkan bahwa prosedur layanan aktivasi IKD di Disdukcapil Kabupaten Sikka telah dilaksanakan sesuai dengan ketentuan dan pedoman teknis yang berlaku, yang meliputi tahap persiapan, verifikasi, dan aktivasi. Petugas pelayanan memiliki peran penting sebagai fasilitator dan pendamping masyarakat dalam proses aktivasi IKD. Namun demikian, pelaksanaan layanan masih menghadapi berbagai kendala, antara lain keterbatasan jaringan internet, keterbatasan sumber daya manusia, serta rendahnya literasi digital sebagian masyarakat. Respons masyarakat terhadap layanan IKD bersifat beragam, di mana sebagian telah merasakan manfaat layanan digital, sementara sebagian lainnya masih ragu untuk menggunakannya. Ditinjau dari perspektif pelayanan publik, layanan aktivasi IKD merupakan bentuk inovasi pelayanan berbasis e-government yang progresif, namun efektivitas dan efisiensinya belum sepenuhnya optimal. Oleh karena itu, diperlukan penguatan infrastruktur, peningkatan kapasitas aparatur, serta strategi sosialisasi yang berkelanjutan agar layanan IKD dapat meningkatkan kualitas pelayanan administrasi kependudukan secara inklusif dan berkelanjutan